Modern Approaches in Meteotsunami Research and Early Warning - Vilibić, Ivica; Šepić, Jadranka; Rabinovich, Alexander B.; Monserrat, Sebastian (Frontiers in Marine Science, 2016)
The understanding of meteotsunamis - significant atmospherically generated long ocean waves in the tsunami frequency band - has advanced considerably during the last two decades. Scientists and specialists use near-field in situ data and remote observations, as well as atmospheric and ocean modelling, to study destructive events. The phenomenon has been reported and investigated worldwide, indicating its relevance within other marine natural hazards and demonstrating the urgent need for meteotsunami warning systems for certain countries. In this paper we summarize the present knowledge of the phenomenon, identify particular research gaps, and propose near-future critical components of meteotsunami research. We emphasize a potential concept of merging yet-to-be-developed meteotsunami warning systems and existing tsunami or multi-hazard early warning systems.